A novel disk-based detection method with superior sensitivity for β-lactamase production in third-generation cephalosporin-resistant Enterobacteriaceae. Issue 5 (May 2019) - Sakanashi, Daisuke; Miyazaki, Narimi; Kawamoto, Yuzuka; Ohno, Tomoko; Yamada, Atsuko; Koita, Isao; Suematsu, Hiroyuki; Hagihara, Mao; Asai, Nobuhiro; Koizumi, Yusuke; Yamagishi, Yuka; Mikamo, Hiroshige
Abstract: Objective: Current phenotypic methods for extended-spectrum β-lactamase (ESBL), AmpC β-lactamase (AmpC), and carbapenemases fail to detect isolates that co-produce other classes of β-lactamases. In this study, we have developed a novel assay (Applied Multiplex Disk Method: AMU-DM) for the phenotypic detection and identification of β-lactamases produced by Enterobacteriaceae . Methods: We evaluated the performance of the method by comparison with PCR results for 78 Enterobacteriaceae clinical isolates that were positive by the ESBL screening test and negative by the ESBL confirmation test. Additionally, one NCTC strain and four ATCC strains were also included in the test population for the study as reference. Results: For 79/83 (95%) isolates tested, the AMU-DM results matched those obtained by PCR. The concordance rates were 31/31 (100%), 11/11 (100%), 3/3 (100%), 0/1 (0%), 15/15 (100%), 16/19 (84%), and 3/3 (100%) for AmpC, ESBL and AmpC co-production, Klebsiella pneumoniae carbapenemase (KPC), KPC and ESBL co-production, metallo β-lactamase (MBL), MBL and ESBL co-production, and MBL and AmpC co-production, respectively. Conclusion: The AMU-DM is convenient to perform, economical, and highly sensitive in identifying ESBLs, AmpCs, and carbapenemases. Our method may be useful in clinical settings for the implementation of relevant infection control measures and for surveillance purposes.